Tensile deformation of a Cu mosaic crystal along the [110] direction studied by time of flight neutron transmission - Santisteban, Javier Roberto (2006)
We studied the plastic deformation of a Cu monochromator loaded in tension along the [110] direction between 0 and 4% equivalent shear strain. We tracked the changes in the orientation and mosaicity of the specimen at several locations simultaneously by analysing the neutron spectra transmitted by the sample. We found that an initial misalignment between different regions of the specimen decreases as deformation proceeds, to reach a minimum at 2% shear strain. On the other hand, the mosaicity of most reflections changes linearly from 10 minutes to 30 minutes, except for the [200] reflection, which presents a more complex behaviour. The experiments used a novel transmission technique involving a polychromatic neutron beam and a pixellated time of flight detector. The technique exploits sharp dips in intensity present in the transmitted neutron spectrum, corresponding to the neutrons removed from the beam after being diffracted by the crystal planes.